Factors influencing the potential of rafting dispersal - analysis of patterns and causal mechanisms along the geographic range of intertidal species on the coast of Chile - López Arriagada, Boris Alejandro
Several studies, using both molecular and ecological evidence, confirm that rafting contributes to population connectivity and range expansion of many species. However, there is also indication that the effectiveness of rafting transport of species to establish in new habitats is limited. This suggests that transport might not be the limiting factor for the dispersal of species but that other factors (ecological or physiological) may restrict the colonization potential of these species. Also, this effective dispersal of a species could vary within its geographic range. The aim of this study was to assess the dispersal patterns of the floating bull kelp Durvillaea antarctica (Chamisso) Hariot 1892 and its associated epibionts along the continental coast of Chile (28°S-42°S) as well as to examine which mechanisms affect dispersal and connectivity of their populations within the geographic range of the continental clade of D. antarctica. It was proposed that ecological factors are more important in the effective dispersal of individuals of D. antarctica in central populations of its geographic range, while in peripheral populations reproductive and functional characteristics of the species are more important; deviations from the predictions of the effective dispersal within the geographic range could be due to local oceanographic conditions. The spatio-temporal variability of stranded bull kelps on beaches (Chapter 1), showed that strandings and morphometric characteristics of rafts varied strongly according to biogeographic districts along the coast of Chile during three consecutive years. The bimonthly study of strandings on three beaches (32°S, 36°S and 39°S) during three consecutive years (Chapter 2) confirmed the spatial pattern that higher stranded biomasses were observed in northern and southern beaches than central beaches. Furthermore, there was a strong seasonal pattern of kelp strandings that was also related to the intensity of local storms. A large-scale survey of rafted holdfasts (28°S-42°S) and a small-scale survey of benthic holdfasts (31°S-32°S) (Chapter 3) showed that the proportion of males and females traveling together in coalescent holdfasts of D. antarctica was low (between 5%-17%). Likewise, the functional capacity analysis indicated that there were no differences in pigment and florotanine concentrations according to the sex of the individuals. The spatio- temporal evaluation of the diversity of epibionts on holdfasts of stranded bull kelps (Chapter 4) showed that sessile species were the most frequent associated epibionts. Also, taxonomic richness of epibionts was higher in southern biogeographic districts (33°S-42°S) than northern ones (28°S-33°S), increasing in summer compared to winter. Habitat-forming species (e.g. mytilid mussels, non-buoyant seaweeds) favoured co-occurrences with other epibionts within a holdfast of D. antarctica, being associated with range extensions of epibionts, particularly in the southern zone (33°S-42°S). Phylogeographic patterns of two epiphytic seaweeds from the genus Gelidium frequent on holdfasts of stranded D. antarctica were contrasting (Chapter 5). Gelidium lingulatum had high genetic diversity, but its genetic structure did not follow a geographic pattern, which could be explained mainly by rafting dispersal via floating bull kelps. On other hand, G. rex had less genetic diversity with a shallow genetic structure, and a phylogeographic break coinciding with the phylogeographic discontinuity described for the region between 29°S–33°S, which suggests short-distance dispersal events. The results indicate that D. antarctica has an important dispersal potential through floating specimens and for transport of associated species, but there are strong spatio-temporal fluctuations in the availability of floating specimens that return to the coast that would affect their eventual successful immigration in other areas. Annual cycles of growth of the benthic populations of bull kelps, the availability of potential primary substratum, the exploitation of their natural beds, and oceanographic and topographic features at regional (i.e. local upwelling, river plumes), and larger scales (i.e. El Niño) might explain the patterns observed in this study. Overall, the results suggest that the reproductive and functional characteristics of floating individuals are not limiting in the effective dispersal capacity and consequent low connectivity of their benthic populations along the Chilean coast compared to local oceanographic features, and demographic factors of resident benthic populations. Hence, this study shows that the effectiveness of rafting dispersal via floating seaweeds in temperate regions vary strongly along the geographic range of the species, as well as on time scales. Local currents and wind regimes generate retention zones for floating supplies that limit the arrival to other areas. In general, the findings of this thesis suggest that at low-latitude range limits of a species the physiological stress suppresses the dispersal potential of floating seaweeds, while at high-latitude range limits, the fluctuations in raft availability and ecological interactions with established benthic communities affect population connectivity.